Community Economic Empowerment Strategy Through Development Policy - Mohamad Iyos Rosyid; Ahmad Mufarrihum; Sururi Faturohman (HK-Publishing, 2024)
Abstract This study aims to analyze community economic empowerment strategies implemented through development policies in Cikeusik District, Pandeglang Regency. While Cikeusik District possesses significant local economic potential, it still faces challenges in optimizing community welfare. A descriptive qualitative research method was employed, utilizing data collection techniques such as in-depth interviews, field observations, and document analysis. The findings indicate that the government has established an economic foundation through the development of village road connectivity, agricultural and maritime production facilities, and free MSME licensing services, alongside the creation of economic institutions such as KUBE (Joint Business Groups) and BUMDes (Village-Owned Enterprises). However, these strategies have not yet optimally achieved sustainable economic self-reliance, largely due to the dominance of a top-down, short-term, and output-oriented approach. Key obstacles identified in the field include the fact that most BUMDes are effectively dormant, the strong grip of conventional middlemen networks, low levels of digital and financial literacy among local entrepreneurs, and weak horizontal coordination between agencies. The study concludes that there is a need to reorient strategies toward a participatory (bottom-up) model and strengthen multi-stakeholder synergy to transform local potential into resilient prosperity. Keywords: Economic Empowerment, Development Policy, Community.